2004
DOI: 10.1243/095440704773599917
|View full text |Cite
|
Sign up to set email alerts
|

A thermomechanical model of a direct injection diesel engine piston

Abstract: This article presents a three-dimensional finite element full analysis, which describes the thermomechanical behaviour of a direct injection diesel engine piston. The piston moving in a complex environment is exposed to several interactions during engine operation. The thermomechanical model takes in account the most important load. The piston is subjected to the coupled action of the thermal loads due to the transfer of heat from the head to the body and the mechanical load represented by the combustion press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The convective heat transfer coefficient in the waterjacket, h water , is used to calculate R 4 [5]. The values of convective heat transfer coefficients for each cylinder are shown in Table 3.…”
Section: The Ring Land and Skirt Thermal Boundary Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…The convective heat transfer coefficient in the waterjacket, h water , is used to calculate R 4 [5]. The values of convective heat transfer coefficients for each cylinder are shown in Table 3.…”
Section: The Ring Land and Skirt Thermal Boundary Conditionmentioning
confidence: 99%
“…His numerical results matched with experiment well. Abbas et al [5] developed a threedimensional finite element full analysis which describes the thermo-mechanical behavior of direct injection diesel engine piston. The piston was subjected to the coupled action of thermal and mechanical loads.…”
Section: Introductionmentioning
confidence: 99%
“…He showed that skirt contours play an important part in the reduction of scuffing and friction. Finite element models of pistons for high-speed direct injection (HSDI) diesel engines were developed and showed the influence of the thermal interaction on the design and development of pistons [7,8].MTahar Abbes et al [9] described thethermomechanical behaviour of a direct injection diesel engine piston by presenting a three dimensional finite element full analysis.…”
Section: Literature Surveymentioning
confidence: 99%
“…According to the structure of piston head and bore, shown in Figure 3, in order to get the gas temperatures in land volumes and groove volumes, it is important to know the temperature distribution of piston head and bore. In recent years, finite element method has been used to calculate piston temperature [21][22][23][24][25][26][27][28][29]. It should be noticed that after having identified one correlation for one engine, we acknowledge that those correlation parameters are not valid for another engine with similar characteristics.…”
Section: Thermomechanical Analysis Of Piston Based On Using the Invermentioning
confidence: 99%